The nature and properties of soils - Weil, Ray R. (Pearson, 2017)
The Nature and Properties of Soils has been my labor of love for the past 5 years and updates a narrative that has both reflected and helped to shape soil science thinking for more than a century. It has evolved to provide a globally relevant framework for an integrated understanding of the diversity of soils, the soil system and its role in the ecology of planet Earth